Nurses\' Perceptions of Ethical Climate, Ethical Reasoning, and Moral Courage in the Hospital - Seyede Elham Fazljoo; Khadijeh Nasiriani; Najme Zamani; Somaye Azimpor (Iran University of Medical Sciences, 2021)
Background & Aims: The ethical climate of nurses' work environment makes the nurse achieve higher levels of ethical reasoning by participating in decision making. Although making decisions is essential, responding appropriately to situations and overcoming fear requires moral courage. The study aimed to determine the nurses' understanding of the hospital's moral climate, reasoning, and moral courage. Materials & Methods: The present study is a cross-sectional descriptive performed on 87 nurses working in Meybod and Ardakan hospitals in March 2020. The Hospital Ethical Climate Survey (HECS), Nursing Dilemma Test (NDT), and Professional Moral Courage (PMC) questionnaire were used to collect data. Data were analyzed using SPSS software, v. 16, and descriptive and analytical statistics of Pearson, independent t-test. Results: The age range of participants was 24-50 years, with a Mean±SD of 32.97±7.26. The average score of ethical climate was 83.72±17.42, moral reasoning was obtained at 45.00±6.91, and moral courage was 45.55±6.04. Significant differences were found between gender and perception of the Ethical Climate (P=0.03). But other individual characteristics of nurses were not significantly different from the studied variables (P> 0.05). Conclusion: According to the findings, the average score of the three variables of nurses' perception of the ethical climate in the hospital, Moral Courage and moral reasoning, was higher than the average score that It reflects the appropriateness of the Ethical Climate in the hospital and the desirable ability of nurses to deal with moral tensions and critical situations. According to the results, the average score of the three variables of nurses 'perception of the Ethical Climate in the hospital, Moral Courage, and moral reasoning, was higher than the average score, which does not indicate the appropriateness of the moral atmosphere in the hospital and nurses' ability to cope with moral tensions. However, due to the need for continuous upgrading and improvement of organizations and human resources working in it, it is suggested to improve the Ethical Climate of hospitals by planning and using appropriate interventions and to promote Moral Courage and moral reasoning in nurses.